Development of new homogeneous photo-Fenton catalytic systems using oxalic acid and ferric ions in very low concentrations - Quoc Viet Bui; Thuy Vy Phan; Tien Khoa Le (Vietnam Journal of Science, Technology and Engineering, 2021)
Despite its contribution to the economic development of many countries over the last few decades, the rapidly growing global textile industry has raised a wide range of environmental problems via the discharge of high amounts of toxic and non-biodegradable dye molecules into the wastewater. In this work, we proposed to combine oxalic acid and ferric ions in very low concentrations to create new, economic, and effective homogeneous photo-Fenton catalytic systems for the degradation of methylene blue. The effects of ferric concentration, H2C2O4 concentration, pH, and tert-butanol on the catalytic activity were also investigated. According to the experimental results, Fe3+ ions exhibited impressive catalytic performances in the presence of H2C2O4 at concentrations below type B (5.0 mg.l–1) from the Vietnam National Technical Regulation on Industrial Wastewater. Specifically, a ferric concentration of 3.0 mg.l–1, H2C2O4 concentration of 10–3 mol.l–1, and pH value of 3 were found to be the best conditions for MB degradation under UVA light. Furthermore, owing to a very low concentration of ferric ions, iron sludge formation can be avoided after wastewater treatment, which makes the photo-Fenton process suitable for practical applications.